Characterising unmet HIV prevention and treatment needs among young female sex workers and young men who have sex with men in Cameroon: a cross-sectional analysis. (July 2019) - Bowring, Anna L; Ketende, Sosthenes; Rao, Amrita; Mfochive Njindam, Iliassou; Decker, Michele R; Lyons, Carrie; Levitt, Daniel; Olawore, Oluwasolape; Turpin, Gnilane; Fako, Guy H; Fouda, Ghislaine; Tamoufe, Ubald; et al.
Summary: Background: In Cameroon, female sex workers (FSWs) and men who have sex with men (MSM) carry disproportionately high burdens of HIV. Despite specific vulnerabilities and health needs, young key populations remain understudied and underserved in Cameroon owing to legal, ethical, and social challenges. We aimed to assess and compare HIV-related behavioural and structural risks and coverage of HIV prevention and treatment services between young and older key populations to inform implementation strategies. Methods: FSWs and MSM aged 18 years or older were recruited through respondent-driven-sampling for a biobehavioural survey carried out in five Cameroonian cities. Prevalence of HIV, risk, stigma, and health service engagement were compared between young (18–24 years) and older (≥25 years) key populations. Multivariable Poisson regression models, disaggregated by key population, were constructed to estimate prevalence ratios (PR) by age group for HIV service engagement. Findings: Participants were recruited between Nov 30, 2015, and Oct 12, 2016. Among FSWs, 724 (32%) of 2255 were aged 18–24 years, and median age of first transactional or compensated sex was 22 years (IQR 19–28). Among MSM, 840 (63%) of 1323 were aged 18–24 years, and median age of first anal sex was 18 years (IQR 17–21). RDS-adjusted HIV prevalence was 8·5% (95% CI 4·7–15·2) among young FSWs and 12·9% (9·5–18·2) among young MSM. HIV viral suppression (<1000 copies per mL) was evident in 24 (43%) of 56 young and 292 (61%) of 479 older FSWs (p=0·0091) and 40 (34%) of 119 of young and 64 (42%) of 153 older MSM (p=0·17). Young FSWs were less likely than older FSWs to report recent peer education (PR 0·65, 95% CI 0·48–0·88), or membership of an FSW community-based organisation (PR 0·69, 0·55–0·86) and were more likely to report untreated sexually transmitted infection symptoms in the past year (PR 1·29, 1·03–1·61). Young MSM were less likely than older MSM to report an HIV test in the past year (PR 0·88, 0·78–0·98), recent peer education (PR 0·77, 0·62–0·95) and receipt of free condoms (PR 0·77, 0·67–0·89). By key population, condom use and recent experiences of stigma and violence were similar between age groups (p>0·05). Interpretation: Young key populations have similar behavioural and structural risks to older populations but have lower coverage of HIV preventive and treatment services. Achieving an AIDS-free generation in Cameroon and elsewhere in the region necessitates overcoming social and legal challenges and delivering innovative, evidence-based, and human rights-affirming HIV prevention and treatment interventions for young key populations. Funding: PEPFAR, USAID.